Injuries in elite football (soccer) academy: A 4-year observational cohort study of five categories and 515 players - Pulici, L.; Randelli, P.; Pellegrini, A.; Zago, M.; Bellistri, G.; Niccolai, R.; Galli, M.; Dellasette, E.; Tosi, L.; Volpi, P. (International Journal of Sports Science & Coaching, 2024)
Background Youth football (soccer) players in professional teams face a higher likelihood of injury compared to adults. The interplay between football and injury hinges on the contextual environment. Despite this, a gap in knowledge persists regarding the epidemiology within Italian elite football academies.